Analisis Pemanfaatan Artificial Intelligence dalam Mendukung Efisiensi dan Keberlanjutan Operasional Bisnis - Desyria Pratiwi; Yusrina Alyani Tamimi; Heidy Puspa Alyssa (Politeknik Negeri Jakarta, 2026)
The quick improvement of Manufactured Insights (AI) innovation has altogether changed advanced commerce operations. This ponder pointed to analyze the utilization of Counterfeit Insights in supporting operational proficiency and trade maintainability. The inquire about utilized a subjective clear approach utilizing writing consider strategies. Information were collected through writing audit of 20 significant diaries and logical articles, documentation of AI utilization, and coordinate perception through free utilize of AI apparatuses such as ChatGPT and robotization frameworks. Information investigation procedures included coding, categorization, and elucidation. The discoveries uncovered that AI execution contributed emphatically to operational effectiveness through mechanization, time investment funds, taken a toll diminishment, expanded work exactness, and minimization of human blunder. AI too upheld commerce maintainability through digitalization, paperless frameworks, and optimization of asset utilization. Be that as it may, a few challenges were recognized, counting web reliance, information security dangers, and the require for human asset adjustment. The think about concluded that Manufactured Insights incorporates a key part in making effective, exact, and feasible trade operations. Keywords: Artificial Intelligence; Operational Efficiency; Sustainability; Automation; Business Digitalization